2017
DOI: 10.3233/ch-16184
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective effects of remote ischemic preconditioning in coronary angiography

Abstract: RIPC proved nephroprotective effect in prevention of contrast-induced nephropathy in CHD subjects with mild to moderate lowered eGFR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
2
15
1
1
Order By: Relevance
“…We separated 18 studies into three groups according to the dose of CM administered: ≤100 ml group (low) 1 (Cao et al, ; Ferdinandy et al, ; Gholoobi et al, ; Igarashi et al, ), 100–200 ml group (medium) 1 (Balbir Singh et al, ; Bøtker et al, ; Er et al, ; Ferdinandy et al, ; Giricz et al, ; Han et al, ; Hausenloy et al, ; Hausenloy & Yellon, ; Hoole et al, ; Luo et al, ; Moretti et al, ; Narula et al, ; Sadat et al, ; Savaj et al, ; White et al, ; Xu et al, ; Yamanaka et al, ; Zagidullin et al, ; Zhou et al, , ), and >200 ml group (high) 2 (Deftereos et al, ; Sadat et al, ). RIC significantly decreased the incidence of CIN in all three groups (low group: OR = 0.29, 95% CI 0.14, 0.60, p < .05; medium group: OR = 0.47, 95% CI 0.34, 0.64; p < .05; and high group: OR = 0.47, 95% CI 0.26, 0.56; p < .05; Table ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We separated 18 studies into three groups according to the dose of CM administered: ≤100 ml group (low) 1 (Cao et al, ; Ferdinandy et al, ; Gholoobi et al, ; Igarashi et al, ), 100–200 ml group (medium) 1 (Balbir Singh et al, ; Bøtker et al, ; Er et al, ; Ferdinandy et al, ; Giricz et al, ; Han et al, ; Hausenloy et al, ; Hausenloy & Yellon, ; Hoole et al, ; Luo et al, ; Moretti et al, ; Narula et al, ; Sadat et al, ; Savaj et al, ; White et al, ; Xu et al, ; Yamanaka et al, ; Zagidullin et al, ; Zhou et al, , ), and >200 ml group (high) 2 (Deftereos et al, ; Sadat et al, ). RIC significantly decreased the incidence of CIN in all three groups (low group: OR = 0.29, 95% CI 0.14, 0.60, p < .05; medium group: OR = 0.47, 95% CI 0.34, 0.64; p < .05; and high group: OR = 0.47, 95% CI 0.26, 0.56; p < .05; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…RIC significantly decreased the incidence of CIN in all three groups (low group: OR = 0.29, 95% CI 0.14, 0.60, p < .05; medium group: OR = 0.47, 95% CI 0.34, 0.64; p < .05; and high group: OR = 0.47, 95% CI 0.26, 0.56; p < .05; Table ). Furthermore, we compared low‐osmolar and iso‐osmolar contrast agents focusing on renal safety and found that RIC decreased the rate of CIN in the low‐osmolar contrast group (Cao et al, ; Deftereos et al, ; Er et al, ; Hoole et al, ; Igarashi et al, ; Luo et al, ; Menting et al, ; Moretti et al, ; Yamanaka et al, ; Zagidullin et al, ) (OR = 0.32; 95% CI 0.23, 0.45; p < .05); however, RIC was not effective in either the iso‐osmolar contrast agent groups (Balbir Singh et al, ; Gholoobi et al, ) (OR = 0.75; 95% CI 0.31, 1.83; p = .52) or groups for which the contrast media type was not mentioned (OR = 0.66; 95% CI 0.41, 1.06; p = .09; Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations